Dave Bing a life of challenge - Sharp, Drew (Human Kinetics, 2013)
What kind of person loses sight in one eye and then through dedicated practice and honed skills becomes one of the top 50 NBA players of all time? What kind of person, with limited business experience, builds a start-up company into a thriving corporation and is recognized as one of the world's most successful black executives? What kind of person, while running a 50 million business, takes the time to reach out to black youths lacking father figures and provides counsel and support? And what kind of person, instead of enjoying a well-deserved luxurious retirement, chooses to become mayor of a large city that many long ago had written off as dead? Dave Bing, that's who. In Dave Bing, Detroit Free Press sports columnist Drew Sharp chronicles the compelling story of a figure whose sheer will to succeed, refusal to make excuses for setbacks, and efforts to contribute to society set him apart as an anomaly--a man of virtues so rarely found in recent history. His path from Washington D.C. to Syracuse to Detroit is sometimes tumultuous, blazed by hard work, perseverance, and savvy. Much more than the stereotypical tale of celebrity ex-jock who does good, this is a story about a black male who, even as a youngster, determined to conquer whatever challenges came his way. And now, as mayor of Detroit, Bing encounters perhaps his greatest test of all. Faced with entrenched and power-hungry political foes, a series of failed and corrupt predecessors, a work force ill prepared for today's job market, a staggering city debt, and recent health problems, Bing would appear to have little chance of surviving his office. Both the naysayers and optimists would do well to read the book.